Muscle temperature and sprint performance during soccer matches - beneficial effect of re-warm-up at half-time - Mohr, M.; Krustrup, P.; Nybo, L.; Nielsen, J. J.; Bangsbo, J. (Scandinavian Journal of Medicine & Science in Sports, 2004)
The relationship between quadriceps muscle temperature (Tm) and sprint performance was evaluated during soccer matches in 25 competitive players. In one game, Tm was determined frequently (n=9). In another game, eight players performed low-intensity activities at half-time (re-warm-up, (RW), whereas another eight players recovered passively (CON). Tm was 36.0±0.2 °C at rest and increased (P<0.05) to 39.4±0.2 °C before the game and remained unaltered during the first half. At half-time, Tm decreased (P<0.05) to 37.4±0.2 °C, but increased (P<0.05) to 39.2±°C during the second half. In CON and RW, Tm and core temperature (Tc) were similar before and after the first half, but 2.1±0.1 and 0.9±0.1 °C higher (P<0.05), respectively, in RW prior to the second half. At the onset of the second half, the sprint performance was reduced (P<0.05) by 2.4% in CON, but unchanged in RW. The decrease in Tm was correlated to the decrease in performance (r=0.60, P<0.05, n=16). This study demonstrates that in soccer, the decline in Tm and Tc during half-time is associated with a lowered sprint capacity at the onset of the second half, whereas sprint performance is maintained when low-intensity activities preserve muscle temperature.